Zinc Supplementation Prevented Type 2 Diabetes-Induced Liver Injury Mediated by the Nrf2-MT Antioxidative Pathway - Lechu Yu; Yuanyuan Liu; Yichun Jin; Tinghao Liu; Wenhan Wang; Xuemian Lu; Chi Zhang (Journal of Diabetes Research)
Zinc is an essential trace element that is often reduced under the type 1 diabetic condition. Previous studies demonstrated that zinc deficiency enhanced type 1 diabetes-induced liver injury and that zinc supplementation significantly helped to prevent this. Due to the differences in pathogenesis between type 1 and type 2 diabetes, it is unknown whether zinc supplementation can induce a beneficial effect on type 2 diabetes-induced liver injury. This possible protective mechanism was investigated in the present study. A high-fat diet, along with a one-time dose of streptozotocin, was applied to metallothionein (MT) knockout mice, nuclear factor-erythroid 2-related factor (Nrf) 2 knockout mice, and age-matched wild-type (WT) control mice, in order to induce type 2 diabetes. This was followed by zinc treatment at 5 mg/kg body weight given every other day for 3 months. Global metabolic disorders of both glucose and lipids were unaffected by zinc supplementation. This induced preventive effects on conditions caused by type 2 diabetes like oxidative stress, apoptosis, the subsequent hepatic inflammatory response, fibrosis, hypertrophy, and hepatic dysfunction. Additionally, we also observed that type 2 diabetes reduced hepatic MT expression, while zinc supplementation induced hepatic MT expression. This is a crucial antioxidant. A mechanistic study showed that MT deficiency blocked zinc supplementation-induced hepatic protection under the condition of type 2 diabetes. This suggested that endogenous MT is involved in the hepatic protection of zinc supplementation in type 2 diabetic mice. Furthermore, zinc supplementation-induced hepatic MT increase was unobserved once Nrf2 was deficient, indicating that Nrf2 mediated the upregulation of hepatic MT in response to zinc supplementation. Results of this study indicated that zinc supplementation prevented type 2 diabetes-induced liver injury through the activation of the Nrf2-MT-mediated antioxidative pathway.